2013
DOI: 10.4149/bll_2013_068
|View full text |Cite
|
Sign up to set email alerts
|

TUGENDHAT: a pilot randomized study on effects of biventricular pacing in patients with bradycardia pacing indication and normal systolic function on heart failure, atrial fibrillation and quality of life (results of 12 month follow-up)

Abstract: Abstract:Background: Since the late 1990s, a growing number of clinical studies have indicated that long-term permanent right ventricular (RV) apical pacing will induce severe complications such as development of heart failure, increased burden of atrial fi brillation leading to decreased quality of life. Aim of the study: To investigate whether cardiac resynchronization therapy (CRT) using biventricular (BiV) pacing can prevent the development of left ventricular (LV) dysfunction, LV remodelling, worsening of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…TUGENDHAT trial 24 : pilot study, patient‐blinded, randomized crossover trial aimed to investigate if BiV pacing could prevent left ventricular dysfunction, remodeling, worsening of clinical status, and quality of life compared with RV pacing in 6 months for patients with class I indication for permanent cardiac pacing and without established indication for BiV pacing. This study was published as an abstract, and failed to present baseline characteristics, including baseline EF, as well as no report of outcomes of interest, including death, HFHs, QRS duration, and echocardiographic data.…”
Section: Resultsmentioning
confidence: 99%
“…TUGENDHAT trial 24 : pilot study, patient‐blinded, randomized crossover trial aimed to investigate if BiV pacing could prevent left ventricular dysfunction, remodeling, worsening of clinical status, and quality of life compared with RV pacing in 6 months for patients with class I indication for permanent cardiac pacing and without established indication for BiV pacing. This study was published as an abstract, and failed to present baseline characteristics, including baseline EF, as well as no report of outcomes of interest, including death, HFHs, QRS duration, and echocardiographic data.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 4 studies were not RCTs, 4 studies did not report outcomes of interest, 8 studies had different interventions, and 2 studies were excluded for being a study protocol ( Figure 1 ). Of the 14 RCTs which were included in the final analysis, six were cross-over trials [ 19 , 21 , 28 31 ]. Three RCTs compared the effect of TriV to that of BiV [ 23 , 29 , 30 ], and the sample size ranged from 18 to 306 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Although a number of studies demonstrated that BiV pacing was associated with superior outcomes compared to conventional CRT [ 32 ], LUV pacing [ 33 ], and RUV pacing in patients without advanced HF [ 34 ], other studies reported no significant difference in improvement in NYHA scores and reverse remodeling between patients who received BiV pacing and those who received LUV pacing [ 20 , 21 ], as well as between those who received BiV pacing and those who received RUV pacing [ 28 ]. Additionally, patients who failed to respond to BiV pacing responded to LUV pacing [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…CF technology allows a real-time assessment of the catheter-tissue CF. Low CF during PV isolation is a predictor of acute and chronic PV reconnections, and is associated with an increased risk of AF recurrence [7][8][9][10] . In addition, ablation procedures under CF guidance improve the lower recurrence rate of the PV isolation [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Contact-force (CF) catheters provide information to the operator to assess the proximity of the catheter to the endocardium. Low CF during pulmonary vein isolation (PVI) has been shown to be a predictor of acute and chronic PV reconnections, and is associated with an increased risk of AF recurrence [7][8][9][10] . CF has been shown to improve the durability of the PV isolation and empower the efficacy of catheter ablation [11] .…”
Section: Introductionmentioning
confidence: 99%